2008
DOI: 10.1016/j.neulet.2008.05.113
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in neuronal calcium levels are associated with cognitive deficits after traumatic brain injury

Abstract: Traumatic brain injury (TBI) survivors often suffer from a post-traumatic syndrome with deficits in learning and memory. Calcium (Ca(2+)) has been implicated in the pathophysiology of TBI-induced neuronal death. However, the role of long-term changes in neuronal Ca(2+) function in surviving neurons and the potential impact on TBI-induced cognitive impairments are less understood. Here we evaluated neuronal death and basal free intracellular Ca(2+) ([Ca(2+)](i)) in acutely isolated rat CA3 hippocampal neurons u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 34 publications
(73 reference statements)
2
50
0
Order By: Relevance
“…The serum levels of ionized calcium on day 3 were supplemented with protein S-100b and IL6 also on day 3 as part of the theory that calcium is diminished due to neuro-and systemic inflammation. Neuro-inflammation is likely to influence cerebral oedema, as shown in (Figures 1 and 2) [11][12][13]. As an indirect sign, patients with poor outcomes had impaired pupillary reactivity, also detected in our study as poor prognosis in the logistic regression model.…”
Section: Discussionsupporting
confidence: 71%
“…The serum levels of ionized calcium on day 3 were supplemented with protein S-100b and IL6 also on day 3 as part of the theory that calcium is diminished due to neuro-and systemic inflammation. Neuro-inflammation is likely to influence cerebral oedema, as shown in (Figures 1 and 2) [11][12][13]. As an indirect sign, patients with poor outcomes had impaired pupillary reactivity, also detected in our study as poor prognosis in the logistic regression model.…”
Section: Discussionsupporting
confidence: 71%
“…We have demonstrated that CNS injuries such as SE, stroke or traumatic brain injury result in neuronal injury and protracted elevations in hippocampal [Ca 2+ ] i (Rice et al , 1998; Raza et al , 2004; Deshpande et al , 2008b; Deshpande et al , 2010). Since Ca 2+ is a major second messenger molecule, such sustained increases in its levels activate multiple signaling cascades, affect protein transcription and alter gene expression of proteins involved in controlling membrane excitability and synaptic plasticity (DeLorenzo et al , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These alterations in Ca2+ dynamics along with the associated neuronal injury are thought to underlie the chronic effects of SE on producing acquired epilepsy and behavioral and cognitive impairment (Rice et al , 1998; Raza et al , 2004; Deshpande et al , 2008b). This study will evaluate the effects of POX induced SE on the development of the Ca 2+ plateau and neuronal damage to determine if the POX SE model produces similar effects on these processes as seen with pilocarpine and DFP SE.…”
Section: Introductionmentioning
confidence: 99%
“…91 In moderate-severe TBI, Ca 2þ accumulation as measured by isotopelabeled Ca 2þ can persist for up to 1 wk, concomitant with memory deficits in the Morris water maze (MWM). 92 Additionally, Ca 2þ -induced depolarization of the mitochondrial membrane allows electron leakage to oxygen in the electron " Social deficits, anhedonia-like behavior, depressive-like behavior " Microglial activation, delayed Repeat þ postinjury foot shock stress: transport chain, uncoupling oxidative phosphorylation, and suppressing adenosine triphosphate (ATP) synthesis in a CCI model. 93 ATP-dependent pumps are engaged to restore TBI-induced ionic imbalances, resulting in a transient increase in cerebral glucose uptake.…”
Section: Excitotoxicity and Cerebral Blood Flow-metabolism Uncouplingmentioning
confidence: 99%